Digital transformation in education: Teachers competency in Integrating Interactive White Board (IWB) - Ghavifekr, Simin; Wong, Seng Yue (2018)
The main purpose of this study was to disclose the effectiveness of Interactive White Board (IWB) in school settings. More specifically this research intended to investigate on teachers' perceptions about IWB integration in their daily teachings. For this quantitative study, data were collected by distributing a set of survey questionnaire to total of 313 teachers from primary schools in Kuala Lumpur, The collected data were analysed using SPSS (23.V) through descriptive statistical analysis. Findings indicates that teachers possess a positive attitude towards IWB with small to moderate significant value and had indicated themselves as apprentice users or initial users with basic to moderate competent level in using the IWB. The study found that, the best way to strengthen teachers' IWB competence is cultivate teachers with relevant and quality professional development and training.